Method of organizing the structure of a distributed system traffic control in the GRID-systems - Кулаков, А. Ю. (Problems of Informatization and Control, 2009)
Method of organizing the structure of a distributed system traffic control in the GRID-systems based on agent technology is proposed. Set of agents are combined in the overlay system. GRID-system partitioning to the set of virtual private GRID-systems is proposed